Feasibility, effectiveness and cost of a decentralized HCV care model among the general population in Delhi, India. (29th November 2021) - Markby, Jessica; Gupta, Ekta; Soni, Divya; Sarin, Sanjay; Murya, Mugil; Katapur, Preetishirin; Tewatia, Navneet; Ramachandran, Babu Entoor; Ruiz, Ryan Jose; Gaeddert, Mary; Tyshkovskiy, Alexander; Adee, Madeline; et al.
Abstract: Background and aims: India has a significant burden of hepatitis C virus (HCV) infection and has committed to achieving national elimination by 2030. This will require a substantial scale‐up in testing and treatment. The "HEAD‐Start Project Delhi" aimed to enhance HCV diagnosis and treatment pathways among the general population. Methods: A prospective study was conducted at 5 district hospitals (Arm 1: one‐stop shop), 15 polyclinics (Arm 2: referral for viral load (VL) testing and treatment) and 62 screening camps (Arm 3: referral for treatment). HCV prevalence, retention in the HCV care cascade, and turn‐around time were measured. Results: Between January and September 2019, 37 425 participants were screened for HCV. The median (IQR) age of participants was 35 (26‐48) years, with 50.4% male and 49.6% female. A significantly higher proportion of participants in Arm 1 (93.7%) and Arm 3 (90.3%) received a VL test compared with Arm 2 (52.5%, P < .001). Of those confirmed positive, treatment was initiated at significantly higher rates for participants in both Arms 1 (85.6%) and 2 (73.7%) compared to Arm 3 (41.8%, P < .001). Arm 1 was found to be a cost‐saving strategy compared to Arm 2, Arm 3, and no action. Conclusions: Delivery of all services at a single site (district hospitals) resulted in a higher yield of HCV seropositive cases and retention compared with sites where participants were referred elsewhere for VL testing and/or treatment. The highest level of retention in the care cascade was also associated with the shortest turn‐around times.